Resource use efficiency and environmental sustainability in greenhouse agriculture through IoT-based irrigation and fertilization management - Gabriele Pizzileo; Lucio Colizzi; Emanuela Guerriero; Tommaso Adamo; Maria Vincenza Chiriacò (Smart Agricultural Technology, 2025)
Conventional agricultural practices have often shown to lead to significant environmental degradation, including water depletion and greenhouse gas emissions. This is particularly evident in greenhouse farming, where traditional practices usually lack the precision and adaptability needed to effectively address environmental challenges and resource constraints. The integration of Internet of Things (IoT) technologies into greenhouse agriculture offers a significant opportunity to enhance sustainability and optimize resource efficiency. This study evaluates the environmental and agronomic impacts of a sensor-based IoT system designed for the dynamic management of irrigation and fertilization. A comparative analysis was conducted between a conventionally managed greenhouse and an experimental greenhouse equipped with the IoT system, both growing zucchini, eggplant, melon, and strawberry.Results demonstrate that the IoT-equipped greenhouse achieved a notable reduction in greenhouse gas emissions (up to −38%) and water use (−41%), alongside an increase in crop yields (average +89%). These outcomes were obtained with considerably lower fertilizer inputs (average −91%), indicating improved nutrient use efficiency and a reduced environmental burden.These findings suggest possible pathways for enhancing both sustainability and efficiency of vegetable production in greenhouse agriculture. In particular, the study highlights the relevance of IoT systems in promoting efficient resource use while mitigating environmental impacts, thereby supporting the transition toward more sustainable agricultural systems. Furthermore, these results underscore the potential of IoT technologies to support data-driven decision-making in greenhouse agriculture, aligning closely with the European Union’s policy targets which emphasizes the need to reduce dependency on inputs, improve resource use efficiency, and promote environmentally responsible food systems.